KOREAN MUSIC AWARDS AND ABNORMAL STOCK RETURNS - Hafida Nur Chofifah; Ani Wilujeng Suryani (Copernican Journal of Finance & Accounting, 2023)
The global success of the K-pop music industry impacts the investment climate of the entertainment industry in the South Korean stock market. One of the driving factors attracting investors is the awards obtained by the K-pop idols. Hence, this event study investigates whether idols’ receiving awards creates stock abnormal returns (ARs) and cumulative abnormal returns (CARs). We collected five-day stock price data surrounding the events from 2018 to 2019 for the four entertainment companies. Using mean difference tests, we analyzed the movements of the stock returns. Our results show the appearance of positive and negative ARs dan CARs, indicating that investors react differently to the information contained in award announcements. This implies a deviance from the efficient market hypothesis and that investors behave irrationally whom investment decision affects the market. For this reason, companies should select awards when involving their idols.